Structural studies and electronic properties of diamond-like amorphous carbon - Lee, Choon H.; Lambrecht, Walter R L; Kelires, Pantelis C. (My University, 1993)
We investigate the network topology and electronic properties of diamondlike models of a-C. An sp3-rich phase is found most closely to resemble mass-selected ion-beam films. The minority sp2 sites in this network occur rather isolated. The π - π* and π* - σ* splittings in the electronic densities of states are in far agreement with experimental data.
Keywords: Carbon; Electronics; Mathematical models; Electric network topology